OP0113 Homeostatic Regulation of T-Cell Trafficking by a B-Cell Derived Peptide is Lost in Early Rheumatoid Arthritis. (9th June 2015) - McGettrick, H.M.; Chimen, M.; Martin, A.; Barone, F.; Walker, L.; Filer, A.; Raza, K.; Buckley, C.D.; Narendran, P.; Rainger, G.E.
Abstract : Background: A significant component of the pathogenesis of rheumatoid arthritis is driven through inappropriate recruitment of T-cells into the joint. Indeed, targeting T-cell recruitment may moderate the onset, severity and persistence of RA. However, very little is known about the mechanisms by which T-cell migration is regulated during inflammation. Objectives: Here, we examined the ability of adiponectin, an anti-inflammatory adipose tissue-derived cytokine, and PEPITEM (a novel PEP tide I nhibitor of T -cell M igration) to regulate the migration of T-cells in vitro and in vivo . Methods: Peripheral blood lymphocytes were isolated from healthy controls or from treatment naive patients with a new onset of clinically apparent RA. Lymphocytes were treated in the presence or absence of adiponectin (15μg/ml) or PEPITEM (10ng/ml). Ex vivo, lymphocyte migration across tumour necrosis factor alpha and interferon gamma stimulated endothelial cells was assessed using phase-contrast microscopy. In vivo, lymphocyte migration was assessed in a model of zymosan-driven peritoneal inflammation. Results: We observed that adiponectin inhibited the migration of human lymphocytes across inflamed endothelium in a dose dependent manner. This effect was lost when B-cells were absent, but could be regained by the addition of supernatants from adiponectin-stimulated B-cells. Mass spectrometry identified the adiponectin induced B-cell-derived agent as a small peptide, subsequently named PEPITEM. In vitro, PEPITEM blocks T-cell migration by stimulating endothelial cells to release sphingosine-1-phosphate, a known regulator of T-cell migration. In zymosan-induced peritonitis, T-cell recruitment was significantly increased in B-cell deficient animals compared to wild-type controls, and this was ameliorated by treatment with synthetic PEPITEM. B-cells isolated from patients with early RA expressed lower levels of adiponectin receptors compared to healthy controls and were unable to respond to adiponectin. Consequently, T-cells from patients with early RA were released from the inhibitory effects of adiponectin on transmigration. Excitingly the full effect of adiponectin was rescued in vitro by the therapeutic use of exogenous PEPITEM. Conclusions: We have identified a novel endogenous peptide (PEPITEM) mediated pathway that suppresses T-cell recruitment across inflamed endothelium, which is dysfunctional in patients with early RA. We believe this leads to a loss of PEPITEM-mediated suppression of T-cell migration, resulting in the inappropriate accumulation of T-cells in the rheumatoid joint. Thus, deregulation of the adiponectin-PEPITEM axis during early development and/or progression of disease could directly contribute to pathology in RA. Re-establishing PEPITEM function to "turn off" pathological recruitment of T-cells represents a novel and potentially powerful approach to treating patients with early rheumatoid arthritis. Acknowledgements: HMM and MC contributed equally to this work. Disclosure of Interest: None declared